Enhancing Students' Interest in Learning Mathematics through the Use of Information Technology Based Learning Media at MTsN 11 Agam: Meningkatkan Minat Belajar Matematika Siswa Melalui Penggunaan Media Pembelajaran Berbasis Teknologi Informasi Pada MTsN 11 Agam - Endang Susilawati (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This research was conducted at Madrasah Tsanawiyah Negeri (MTsN) 11 Agam. The research method used was a qualitative descriptive method. The aim of this research is to describe the use of information technology-based learning media in mathematics education with the goal of attracting and enhancing students' learning interest. Data was collected through observation, interviews, and documentary studies. Data processing involved data reduction, data presentation, and drawing conclusions. This research emphasizes efforts to increase students' interest in learning mathematics through the utilization of information technology-based learning media at MTsN 11 Agam. The research findings indicate that students' interest in learning mathematics in conventional education tends to be low and declining. However, the use of information technology-based learning media has been proven effective in enhancing students' enthusiasm for learning mathematics. Therefore, it is expected that teachers actively use and promote the use of information technology-based learning media in their teaching practices